(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The external characteristics of aspen (Populus tremula) tree give the only clue to the quality of logs, packing case timber, pulpwood and other roundwood assortments obtained in harvesting. When the tree is bucked into roundwood assortments, the cross sections at the butt and top ends of these assortments may provide additional indicators of the quality such as heart colouring, wetwood, heartwood hard rot and heartwood soft wood. Thus, it becomes important when correlating the occurrence of these imperfections with the quality of sawn timber that is produced from the aspen logs and packing case timber.; Although aspen has a wide distribution throughout Europe, there are no unified quality requirements for roundwood assortments due to lack of scientifically approved information related to wood structure. To identify the fungi caused aspen decay and describe the main anatomical changes generated by the fungi (Phellinus tremulae) Polymerase Chain Reaction laboratory technique were used in the investigation. The main goal of the study is to work out the aspen roundwood, harvested in final felling sites timber strength parameters depending on timber quality characterized data based on the testing methods: moisture content - according to ISO13061-1:2014; density - according to ISO13061-2:2014; compression strength paralel to the grain- according to ISO 13061-17:2017; modulus of elasticity- according to ISO 13061- 4:2014; three point bending strength - according to ISO 13061- 3:2014.; The results of the study might help for practical applications so that this wood specie can be processed more efficiently for the value - added products and thorough knowledge of decay patterns of Phellinus tremulae are likely to assist to establish more accurate quality requirements for roundwood assortments and provide useful information for optimizing tree management programs.